(untitled) (Research, Society and Development, 2022)
Objective: To describe factors that influence the use of contraceptives by adolescentes. Methodology: This is an integrative review regarding the use of contraceptives in adolescence. The research was conducted in June 2021 in the following databases: MEDLINE, LILACS and PubMed. To perform the review, we used descriptors determined based on the Descriptors in Health Sciences (DeCS), they were: "adolescents", "contraceptives", "contraceptives", "teenager" and "contraception". A total of 143 articles were found, however, after inclusion and exclusion criteria, 8 articles were selected. Result: It is seen that even in contemporary times, there are still a range of factors that hinder the use of contraceptive methods by adolescents. Factors such as culture, religion, age group, gender inequality and social class are determinant in choosing a method of protection. In addition, the lack of communication with parents influenced the lack of knowledge of young people about the methods, as well as limited the search for professional care in the health system and support. Conclusion: Although sex education, medical secrecy and access to contraceptive methods, rights guaranteed to adolescents, many of them do not yet have access to family planning. This ends up putting many teenagers in a state of vulnerability when it comes to STIs and early pregnancy.